2010
DOI: 10.1029/2009jb007198
|View full text |Cite
|
Sign up to set email alerts
|

Early Holocene and Late Pleistocene slip rates of the southern Dead Sea Fault determined from 10Be cosmogenic dating of offset alluvial deposits

Abstract: [1] Two sites located along the Wadi Araba Fault (WAF) segment of the Dead Sea Fault are targeted for tectonic-morphological analysis. 10 Be cosmogenic radionuclide (CRN) dating of embedded cobbles is used to constrain the age of offset alluvial surfaces. At the first site a 48 ± 7 m offset alluvial fan, for which 10 Be CRN model ages average 11.1 ± 4.3 ka, yield a slip rate of 5.4 ± 2.7 mm/a, with conservative bounds of 1.3-16.4 mm/a. At the second site the scattered distributions of the 10 Be CRN ages from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 60 publications
8
53
0
Order By: Relevance
“…2). The slip rate of about 5 mm/yr proposed by geodetic studies along the southern part of the DSF is consistent with paleoseimological and geomorphological studies (Klinger et al, 2000;Le Bé on et al, 2010Niemi et al, 2001). Historical records document the strong earthquake potential of the southern DSF, despite a general seismic quiescence over the past few centuries (Ambraseys et al, 1994).…”
Section: Introductionsupporting
confidence: 78%
“…2). The slip rate of about 5 mm/yr proposed by geodetic studies along the southern part of the DSF is consistent with paleoseimological and geomorphological studies (Klinger et al, 2000;Le Bé on et al, 2010Niemi et al, 2001). Historical records document the strong earthquake potential of the southern DSF, despite a general seismic quiescence over the past few centuries (Ambraseys et al, 1994).…”
Section: Introductionsupporting
confidence: 78%
“…Relative ages of alluvial surfaces can be distinguished as a function of surface height above active streams, degree of incision by surficial rills and regressive gullies, surface darkness and geometric relationship between the deposits [e.g., Klinger et al , 2003; Le Béon et al , 2010]. For example, darker surfaces, related to desert varnish and desert pavement, typical in arid areas, indicate older surfaces [ Bull , 1991; Quade , 2001].…”
Section: Morphotectonic Map Of the Wadi Arabamentioning
confidence: 99%
“…These different studies converge to a mean value of 4–6 mm/yr between present and 20 Ma ago. Some, however, suggest that the slip rate could have been as high as ∼10 mm/yr during the late Pleistocene [ Klinger et al , 2000a; Le Béon et al , 2010].…”
Section: Introductionmentioning
confidence: 99%
“…North of the GEA, the DST passes along the Arava (Wadi 'Arabah) Valley. Mapping of offset surface features, aided by field observations, aerial photo analysis, and paleoseismic trenches [e.g., Zak and Freund , ; Garfunkel et al ., ; Ginat et al ., ; Klinger et al ., , ; Niemi et al ., ; Le Béon et al ., , ] and recent gravimetric and magnetic studies [ Haberland et al ., ; ten Brink et al ., ] revealed that the DST traverses the central Arava Valley predominantly as a single, almost continuous, sinistral strike‐slip fault. Modeling of gravity and magnetic data [ ten Brink et al ., , ], and seismic profiles [ Frieslander , ] revealed separate longitudinal basins along the Arava Valley.…”
Section: Previous Workmentioning
confidence: 99%
“…Generalized tectonic settings of the Dead Sea fault or transform (DST) [modified after Le Béon et al ., , and references therein]. The DST separates the Arabian Plate from the Levantine Subplate.…”
Section: Introductionmentioning
confidence: 99%